Penjatuhan Hukuman Pidana Mati terhadap Tindak Pidana Narkotika - Novrianza, Novrianza; Subroto, Mitro (CV RIFAINSTITUT, 2021)
The death penalty can be described as a form of punishment regulated in law number 35 of 2009 which regulates the abuse of narcotics crimes. This death penalty legislation has caused various kinds of confIicts because the death penalty is not in accordance with the 1945 constitution which is contrary to human rights and many also argue that the death penalty must be implemented in order to have a deterrent effect on the perpetrators of narcotics abuse. This form of death penalty is the most cruel and sadistic form of punishment because this punishment kills a person's life. this type of research is done by means of a qualitative approach. The purpose of this study is to find out the imposition of the death penalty for narcotics crimes. Results showed if the application of the death penalty can only be against acts of criminal acts were limits of humanity, threatening the lives of many people, destructive to human life, and may damage the nation's economy. The imposition of the death penalty is not against human rights. along pejustified afirstasan human rights.